Chemopreventive effects of Prunus cerasus L. against human cancer cells & ascites mice models and its phytochemical investigation by LC-Q-TOF-MS/MS - Abid Ali Sheikh; Zahoor Ahmad Wani; Aabid Manzoor Shah; Qazi Parvaiz Hassan; Dilip Manikrao Mondhe; Mahendra Kumar Verma (Elsevier, 2022)
Background: Berries, including cherries and their derived distinctive bioactive leads, are explored for the establishment of therapeutic supplements, owing to their versatile biological applications accompanied with less or no side effects to normal cells. The current research work aimed to identify various phytocomponents of P. cerasus fruit extract (PcMFE) and investigate its chemopreventive properties employing cellular assays coupled with experimental Ascites mice models. Method: LC-ESI-Q-TOF-MS (HRMS) approaches were used for chemoprofiling of P. cerasus methanolic fruit extract (PcMFE). After testing for scavenging capacities on DPPH, radical & lipid peroxidation, the In-vitro anticancer potential was investigated against five distinct human cancer cell lines A-549, THP-1, MCF-7, PC-3 and NCI-H322 using MTT and SRB assays. In case of in-vivo antitumor assessment, PcMFE was investigated against Ehrlich Ascites Carcinoma (EAC) and Methylcholanthrene induced Ascites (Meth-A) experimental mice models. Results: HRMS analysis of PcMFE resulted in identification of 59 compounds belonging to diverse chemical classes. Besides significant antioxidant potential, PcMFE at 50 µg/ml dose blocked 40-100% growth of various cancer cell lines, with maximum (100% growth inhibition) against NCI-H322 showing an IC50 of 5.59 µg/ml and 5 µg/ml respectively in SRB and MTT assays. Execution of apoptosis induced by PcMFE in NCI-H322 cancer cells revealed an increased population of apoptotic cells evidenced through nuclear morphology studies. Moreover, intraperitoneal administration of PcMFE at 200 mg/kg body weight reported 72.31% and 68.69% tumor growth inhibition in EAC & Meth-A mice model, respectively. Conclusions: The present study exhibited that P- cerasus fruit is a valuable source of diverse functional metabolites and may facilitate development of chemopreventive supplements.